Nuclear energy renaissance in the world and its implications in the Middle East - (:unkn) unknown (My University, 2008)
0

Nuclear renaissance means different things to different people. Since not only energy dependent states but also oil producing countries are expressing their desire to go nuclear, it is necessary to add a political dimension to explain the awakened dormant interest in nuclear energy particularly in the Middle East. In this vein, nuclearization reflects a desire to display a nation's power versus others to negotiate a fair share not only with adversaries but with allies as well. With regard to international security the key question is whether nuclear expansion will be limited to reactors only, or will it include enrichment and reprocessing facilities. The growing number of countries that do not possess a domestic reactor base but interested in developing enrichment capabilities for export purposes, makes it difficult to justify why other states should not develop such capabilities.